Zobrazowanie miast północnego Śląska na podstawie wybranych map tego regionu do końca XVIII wieku = Representations of northern-Silesian towns in the region's maps before XIX c. - Buczek, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper shows various graphic representations of northern-Silesian towns in maps from the period of XVI-XVIII c. The maps usually presented the whole of Silesia or itsparticular duchies. The paper' s structure is governed not only by chronology but also by the maps' graphic content, which allows one to see the way town representations developed. Their evolution can be traced from the 1544 first independent map of Silesia by Sebastian Münster to Martin Helwig's great work (and its modifications) to Jonas Scultetus's maps to some of the maps in "Atlas Silesiae" of 1752.
Keywords: Dolny Śląsk - mapy; Dolny Śląsk - miasta; historia - do 18 w.